Effect of colistin combined with sulbactam: 9 g versus 12 g per day on mortality in the treatment of carbapenems resistant Acinetobacter baumannii pneumonia: A randomized controlled trial - Chutchawan Ungthammakhun; Vasin Vasikasin; Waristha Simsiriporn; Piraporn Juntanawiwat; Dhitiwat Changpradub (International Journal of Infectious Diseases)
Background: The current treatment recommendation involves administering a high dose of sulbactam alongside at least one additional agent. However, there remains a lack of data regarding the optimal dosage of sulbactam. We investigated whether administering sulbactam at a dosage of 12 g/day decreases the mortality rate among patients with CRAB pneumonia compared to 9 g/day. Methods: The study was an open-label, superiority, randomized controlled trial conducted at Phramongkutklao Hospital between September 2019 and September 2023 in patients diagnosed with CRAB. Participants were randomly assigned to receive a combination of colistin with either 9 or 12 g/day of sulbactam. The primary endpoint was the all-cause mortality rate at 28 days postrandomization. Results: Among the 138 participants, there was a trend towards a lower mortality rate in the 12 g/day group (59.4% vs. 47.8%; P = 0.158). After adjusting for factors associated with mortality, a lower mortality was observed in the 12 g/day group (adjusted HR 0.54 [95% CI 0.33-0.87]; P = 0.0110). The microbiological cure rate at day 7 was higher in the 12 g/day group (73.2% vs. 89.4%; P = 0.02). Conclusions: Colistin in combination with sulbactam at a dosage of 12 g/day may improve mortality compared to 9 g/day.